FORMULASI EMULSI ORAL MINYAK JINTAN HITAM (Nigella sativa) DENGAN BAHAN PENGENTAL - Tomagola, M. Ilham (Fakultas Farmasi UMI, 2013)
The aim of this research was to determine the type and thickening agent variation which of result stable emulsion. There were three thickening agent, they are CMC sodium, Acacia gum and xanthan gum used in formula. Those three formula then evaluated by accelarated condition method by which the parameter were organoleptic, type of emulsion, creaming volumen, viscosity and type of flow, dispersed globule observation before and after the condition. Organoleptic result showed that there were nothing different in formula II. Type of emulsion showed that those three formula were o/m emulsion. There were nothing creaming volume in formula I and II. Statistic analyze in viscosity measurement and yield value, rheogram curve showed close each other, dispersed globule there were not undergo aggrregation in formula I and II before ad after accelarated condition. Of those parameter the conclusiÃ³n was formula II is stable one.Key word : Formulation, Emulsion, Nigella sativa, Â Agent Variation